Comparing phosphatised galleried stereom of Ordovician Cincinnaticrinus to modern Endoxocrinus illustrates preservation by micromolding - Benjamin F. Dattilo; Rebecca L. Freeman; David F. Wright; David L. Meyer; James R. Thomka; Samuel Sheray; Michael Harrison; Christopher D. Aucoin (Facies, 2026)
Fossil echinoderm ossicles are often occluded by syntaxial overgrowths which obscure stereom. Phosphatized ossicles from insoluble residues show fine microstructure. We investigated phosphatized stereom in Cincinnaticrinus columnals in insoluble residues from the Ordovician around Cincinnati, Ohio USA. Microstructures appeared to be stereom micromolds. We tested this hypothesis by examining residue and thin sections of undissolved sample using light microscopy, SEM and EDS, resulting in these observations: (1) calcite within phosphatized ossicles is optically aligned and parallel to stem; (2) phosphate deposited centripetally from calcite surfaces, often incompletely filling cavities, leaving a central vug; (3) while calcite is inclusion-free, phosphate contains siliciclastic inclusions from surrounding sediments. These observations suggest that calcite is original, and phosphate was deposited as micromolds. To confirm the phosphatic micromold hypothesis, we compared internodal columnals from the extant isocrinid Endoxocrinus from the Florida Straits using fracture surfaces and epoxy-impregnated thin sections. We then dissolved the thin section calcite, leaving epoxy micromolds for comparison. Schematic 3-D models summarize our reconstructions of structure of the crinoids in both original calcite and micromolds. Through-going solid cylinders are present in Cincinnaticrinus phosphate and Endoxocrinus epoxy molds. In Endoxocrinus , these are molds of stereomic galleries complete with ligaments, confirming Cincinnaticrinus phosphate is also moldic. Galleried stereom of the two crinoids differs in structural details, a divergence that is consistent with phylogenetic evidence of through-going ligaments in an early common ancestor. Preservation by phosphatic micro-molding, interpreted as preserved negative space, facilitates study of stereomic features supporting crinoid soft tissues.

Where and how can WASH work? Understanding limited impacts from a randomized control trial of water, sanitation, and hygiene interventions in a high burden setting - Alicia N.M. Kraay; Andrew F. Brouwer; Mondal H. Zahid; Sammy Njenga; John M. Colford; Matthew C. Freeman; Joseph N.S. Eisenberg (International Journal of Hygiene and Environmental Health, 2026)

Examining the effect of neighborhood sanitation coverage on childhood diarrheal disease in rural Bangladesh - Hannah Van Wyk; Andrew F. Brouwer; Jesse Contreras; Mahbubur Rahman; Mahfuza Islam; Amy J. Pickering; Benjamin F. Arnold; Stephen P. Luby; John M. Colford; Matthew Freeman; Ayse Ercumen; Joseph N.S. Eisenberg (International Journal of Hygiene and Environmental Health, 2026)

Sowing the seeds of wildlife-friendly gardening: does a garden biodiversity assessment promote uptake of pro-biodiversity gardening behaviours? - Yolanda van Heezik; Jacqueline Theis; Danielle F Shanahan; Claire Freeman; Maibritt Pedersen Zari; Christopher K Woolley (Urban Ecosystems, 2026)
Residential gardens have the potential to support native biodiversity across cities. Certification programmes designed to motivate residents to perform pro-biodiversity gardening actions require a formal process of garden biodiversity assessment. We evaluated whether a garden biodiversity assessment process was effective at motivating pro-biodiversity gardening behaviours. A one-off garden assessment accompanied by feedback was trialled on 89 residents in 2020/2021. Four years later we surveyed this group and a matched control group to determine whether the assessment had a motivating and long-lasting positive effect on pro-biodiversity gardening. Results were mixed: while 57% reported the assessment did not influence subsequent gardening decisions, 38.5% confirmed that the assessment process had motivated the changes they made and 56% said it helped them understand at least a little better how they could enhance biodiversity in their garden. This understanding was positively associated with how useful they rated their tailored feedback but was not associated with their biodiversity score. The two groups didn’t differ in the extent to which biodiversity enhancement was considered when making changes, and a larger proportion of the control group made biodiversity-positive changes. The number of changes made was not associated with age, income, education, years at the address, bird knowledge, or environmental engagement, but was positively associated with their nature connection score. While we provide some evidence to support the use of biodiversity assessments, ongoing support in the form of collaborative partnerships between gardeners and local government could be more effective at achieving favourable biodiversity outcomes.

Effect of water, sanitation, and hygiene on childhood growth in Ethiopia: a cluster-randomized trial - Tahvi Frank; Isabel J.B. Thompson; Solomon Aragie; Dionna M. Wittberg; Wondyifraw Tadesse; Adane Dagnew; Dagnachew Hailu; Jason S. Melo; Taye Zeru; Zerihun Tadesse; Benjamin F. Arnold; Matthew C. Freeman; et al. (International Journal of Hygiene and Environmental Health, 2026)

Necroptosis induced by MLKL overexpression in liver triggers cellular senescence and leads to chronic inflammation and fibrosis - Ramasamy Selvarani; Sunho Lee; Mani Saminathan; Puvarajan Boovalingam; Kavitha Kurup; Kevin Pham; Roman F. Wolf; Willard M. Freeman; Archana Unnikrishnan; Arlan Richardson (GeroScience, 2025)
Cellular senescence and necroptosis are two cell fates, which trigger an inflammatory response and increase with age, that have been proposed to play a role in inflammaging. In this study, we performed the first study to directly test the possible interaction between necroptosis and cellular senescence. Using a novel Mlkl -KI mouse model, we were able to specifically induce (~ 4-fold) the overexpression of MLKL, the necroptotic executioner, in hepatocytes (h Mlkl -KI mice). The overexpression of MLKL led to increased necroptosis and cell damage/death in liver, as shown by increased levels of MLKL-oligomers, TUNEL staining, and Ki-67 staining in the livers, as well as increased ALT activity and HMGB1 levels in the plasma. The increase in necroptosis was paralleled by an increase in cellular senescence. We observed increased levels of p16 INK4A and p21 Clip1/Waf1 as well as SASP-factors. As expected, inflammation, as measured by the levels of proinflammatory factors and mononuclear cell clusters, was increased in the h Mlkl -KI mice. Transcriptomic analysis revealed that MLKL overexpression altered the expression of genes involved in cellular senescence, inflammation, and drug metabolism. The increase in inflammation, necroptosis, and cellular senescence in the livers of 6-month-old h Mlkl -KI mice was associated with an increase in liver fibrosis. The data from our study suggest that necroptosis has the potential of inducing inflammation through two pathways: (1) the initial inflammatory storm triggered by DAMPs released from necroptotic, dying cells and (2) SASP-factors produced by senescent cells that were induced by necroptosis. Graphical abstract

Spring awakening? Seasonal controls on halomethoxybenzenes in arctic waters - Danielle Haas Freeman; Emma Shipley; Penny Vlahos; Mats Tysklind; Terry F. Bidleman (Science of The Total Environment, 2025)

Priorities, concerns, and potential compromises amongst urban forest stakeholders: international lessons from Aotearoa New Zealand - Thomas F. Carlin; Tim Barnard; Toby Chapman; Justin Morgenroth; Daniel R. Richards; Robyn Simcock; Jonathon Avery; Zoë Avery; Yvette Dickinson; Kate Elliot; Claire Freeman; Derek Hayes; et al. (Urban Ecosystems, 2025)
Urban forests provide numerous benefits including habitat for wildlife, improving human health, purifying air and water, and preventing and mitigating the effects of climate change. The need to protect and improve our urban forests will only increase as populations increase and cities densify and expand over time. However, urban forest establishment and maintenance is challenging due to a lack of effective policies, delays, lack of communication, inappropriate targets, and lack of recognition, disunity, or resourcing amongst stakeholders. Here we present the results from a joint urban forest symposium-workshop that sought to determine the priorities and challenges of different stakeholder groups in New Zealand, including arborists, ecologists, non-ecologist researchers, indigenous peoples, and planners. We synthesise these lessons as recommendations to improve urban forest planning, design, establishment, and minimise conflicts between stakeholder groups. While the highest priorities of each stakeholder group are fairly distinct, there are high levels of overlap in the general priorities and challenges they face in working towards advancing those priorities. We suggest a 3-phase framework to deliver progress that broadly considers (1) data collection, (2) policy development, and (3) resource development. We suggest this framework should be supported by continual monitoring and data sharing, an increased investment in green employment and education, and further recognition of urban foresters, indigenous communities, and ecologists. We suggest that an inclusive approach based on a shared understanding of forest values and removing barriers is most likely to result in long-term success.

P28-35 Xylene: weight of evidence approach case study to determine the need for an extended one generation reproductive study with a developmental neurotoxicity animal cohort - L. Higgins; C. Haines; F. Faulhammer; M. Rooseboom; N. Aygun Kocabas; J.H. Arts; A. Cordova; E. Freeman; M. Nahar; E. Richmond; S. Schneider; K. Morris-Schaffer (Toxicology Letters, 2025)

Pacific Northwest birds have shifted their abundances upslope in response to 30 years of warming temperatures - Benjamin G. Freeman; Harold N. Eyster; Julian M. Heavyside; Daniel A. Yip; Monica H. Mather; F. Louise Waterhouse (Ecology, 2025)
Mountain species are predicted to respond to warming temperatures by moving to higher elevations that remain relatively cool. Species can track warming by shifting their entire distributions upwards (the “escalator to extinction” hypothesis) or by increasing in abundance in the upper portion of their elevational range while maintaining stable elevational limits (the “upslope lean” hypothesis). Alternatively, mountain species may not change their abundance or distribution despite climate change (the “persist‐in‐place” hypothesis). Here we evaluate these three contrasting hypotheses by analyzing responses of breeding forest bird species to three decades of warming in southwestern British Columbia, Canada. Consistent with the upslope lean hypothesis, species' optimum elevations (elevations of highest abundance) increased by an average of 126 m, approximately tracking upslope movements in temperature isotherms. In contrast, species' elevational range limits were stable on average, contra the escalator to extinction hypothesis. Many individual species had stable distributions and abundances, and species with upslope abundance increases typically maintained stable abundances within the lower elevation portions of their range. Taken together, most species in our study region appear to be responding neutrally or favorably to warming temperatures. Nevertheless, one mountain species, the Canada Jay, Canada's national bird, is declining and vulnerable to the escalator to extinction within our study region. Overall, we emphasize the importance of empirical data—and abundance data in particular—when evaluating mountain species' vulnerability to climate change.

Shifting, expanding, or contracting? Range movement consequences for biodiversity - Jedediah F. Brodie; Benjamin G. Freeman; Philip D. Mannion; Anna L. Hargreaves (Trends in Ecology & Evolution, 2025)

Impact of water, sanitation, and hygiene indicators on enteric viral pathogens among under-5 children in low resource settings - Rina Das; Md. Nasif Hossain; Myron M. Levine; Karen L. Kotloff; Dilruba Nasrin; M. Jahangir Hossain; Richard Omore; Dipika Sur; Tahmeed Ahmed; Robert F. Breiman; A.S.G. Faruque; Matthew C. Freeman (Science of The Total Environment, 2025)

A global systematic review of the cultural ecosystem services provided by wetlands - Kevin A. Wood; Lucy L. Jupe; Francisca C. Aguiar; Alexandra M. Collins; Scott J. Davidson; Will Freeman; Liam Kirkpatrick; Tatiana Lobato-de Magalhães; Emma McKinley; Ana Nuno; Jordi F. Pagès; Antonella Petruzzella; et al. (Ecosystem Services, 2024)

Review of skeletal carbonate mineralogy of brachiopods with new material from New Zealand - Abigail M. Smith; David F. Freeman; Ian S. Dixon‐Anderson; Daphne E. Lee (New Zealand Journal of Marine and Freshwater Research, 2024)
We combine published and new mineralogical data on most major taxa of brachiopods from all over the world, to investigate patterns and controls on brachiopod carbonate mineralogy. Measurements of 1726 specimens in 162 species (including 56 fossil species) ranged from 79°N to 74°S and from intertidal to almost 4000 m deep. Calcareous brachiopods mostly create strong resilient valves of very low‐Mg calcite ( = 1.3 wt% MgCO 3 ). The substrate‐cemented Craniida ( = 8.9 wt% MgCO 3 ) and Thecideida ( = 6.5 wt% MgCO 3 ) are unusual in precipitating calcite with higher Mg content. This is the first study to find bimineralic brachiopods; a few species show a combination of low‐Mg ( = 0.8 wt% MgCO 3 ) and intermediate‐Mg calcite ( = 7.2 wt% MgCO 3 ) ( sensu Smith AM, Key MM Jr, Gordon DP. 2006. Skeletal mineralogy of bryozoans: taxonomic and temporal patterns. Earth‐Science Reviews. 78:287–306.). While Mg in calcite varies systematically among valve layers and sometimes along the growth axis, we found no consistent difference between valves of the same individual. A weak latitudinal signal indicates some overall temperature control of Mg, but in general, brachiopods are active calcifiers, precipitating low‐Mg calcite even when Mg:Ca ratio in seawater is high. The drivers on brachiopod mineralogy are individual, environmental, and phylogenetic – resulting in complex variability.

The socioecological benefits and consequences of oil palm cultivation in its native range: The Sustainable Oil Palm in West Africa (SOPWA) Project - Michael D. Pashkevich; Cicely A.M. Marshall; Benedictus Freeman; Valentine J. Reiss-Woolever; Jean-Pierre Caliman; Julia Drewer; Becky Heath; Matthew T. Hendren; Ari Saputra; Jake Stone; Jonathan H. Timperley; William Draper; et al. (Science of The Total Environment, 2024)

Population expansion and intensification from a Malthus-Boserup perspective: A multiproxy approach in Central Western Argentina - Eva A. Peralta; Jacob Freeman; Adolfo F. Gil (Quaternary International, 2024)

Corrigendum to “Elevated parkinsonism pathological markers in dopaminergic neurons with developmental exposure to atrazine” [Sci. Total Environ. 908 2024: Article 168307] - Han Zhao; Junkai Xie; Shichen Wu; Xihui Zhao; Oscar F. Sánchez; Sehong Min; Sayan Dutta; Jean-Christophe Rochet; Jennifer L. Freeman; Chongli Yuan (Science of The Total Environment, 2024)

Elevated parkinsonism pathological markers in dopaminergic neurons with developmental exposure to atrazine - Han Zhao; Junkai Xie; Shichen Wu; Xihui Zhao; Oscar F. Sánchez; Sehong Min; Jean-Christophe Rochet; Jennifer L. Freeman; Chongli Yuan (Science of The Total Environment, 2024)

Missing the middle: Deep cyanobacteria layers pose a “known unknown” risk to water security - Kevin J. Erratt; Irena F. Creed; Erika C. Freeman; Charles G. Trick (Water Security, 2023)

Characterization of novel mouse models to study the role of necroptosis in aging and age-related diseases - Ramasamy Selvarani; Hoang Van Michelle Nguyen; Nidheesh Thadathil; Roman F. Wolf; Willard M. Freeman; Christopher D. Wiley; Sathyaseelan S. Deepa; Arlan Richardson (GeroScience, 2023)
To study the impact of necroptosis-induced chronic inflammation on age-related diseases and aging, two knockin mouse models ( Ripk3 -KI and Mlkl -KI) were generated that overexpress two genes involved in necroptosis ( Ripk3 or Mlkl ) when crossed to Cre transgenic mice. Crossing Ripk3 -KI or Mlkl -KI mice to albumin-Cre transgenic mice produced hepatocyte specific hRipk3 -KI or hMlkl -KI mice, which express the two transgenes only in the liver. Ripk3 and Mlkl proteins were overexpressed 10- and fourfold, respectively, in the livers of the hRipk3 -KI or hMlkl -KI mice. Treating young (2-month) hRipk3 -KI or hMlkl -KI mice with carbon tetrachloride (CCl 4 ), a chemical inducer of oxidative stress, resulted in increased necroptosis (Mlkl-oligomers) and inflammation in the liver compared to control mice receiving CCl 4 . Mlkl-oligomerization also was significantly increased in old (18-month) hRipk3 -KI and hMlkl -KI mice compared to old control (Cre negative, Ripk3 -KI and Mlkl -KI) mice. The increase in necroptosis was associated with an increase in inflammation, e.g., inflammatory cytokines (TNFα, IL-6) and macrophage markers (F4/80, CD68). Importantly, steatosis (triglycerides) and fibrosis (e.g., picrosirius red staining, hydroxyproline levels, and transcripts for TGFβ, Col1α1, and Col3α1) that increase with age were significantly higher in the livers of the old hRipk3 -KI or hMlkl -KI mice compared to old control mice. In addition, markers of cellular senescence were significantly increased in the livers of the old hRipk3 -KI and hMlkl -KI mice. Thus, the first mouse models have been developed that allow researchers to study the impact of inducing necroptosis in specific cells/tissues on chronic inflammation in aging and age-related diseases.

25 The potential impact of female body shape on rider posture and scores received from dressage judges - S. Forino; L. Cameron; N. Stones; V. Lewis; F. Freeman (Journal of Equine Veterinary Science, 2023)

Juxtaposition of intensive agriculture, vulnerable aquifers, and mixed chemical/microbial exposures in private-well tapwater in northeast Iowa - Paul M. Bradley; Dana W. Kolpin; Darrin A. Thompson; Kristin M. Romanok; Kelly L. Smalling; Sara E. Breitmeyer; Mary C. Cardon; David M. Cwiertny; Nicola Evans; R. William Field; Michael J. Focazio; Laura E. Beane Freeman; et al. (Science of The Total Environment, 2023)

Energy-effective and low-cost carbon capture from point-sources enabled by water-lean solvents - Yuan Jiang; Paul M. Mathias; Richard F. Zheng; Charlies J. Freeman; Dushyant Barpaga; Deepika Malhotra; Phillip K. Koech; Andy Zwoster; David J. Heldebrant (Journal of Cleaner Production, 2023)

Host phylogeny and elevation predict infection by avian haemosporidians in a diverse New Guinean bird community - Geoffrey C. F. Lau; Alexandra M. Class Freeman; Paulo Pulgarín‐R; Carlos Daniel Cadena; Robert E. Ricklefs; Benjamin G. Freeman (Journal of Biogeography, 2023)
Aim The biotic interactions hypothesis predicts that interactions between species are stronger at lower elevations compared to higher elevations. We tested whether this prediction is met by examining elevational patterns in avian haemosporidian infections in New Guinean birds. Location YUS Conservation Area, Papua New Guinea. Taxon Birds and haemosporidia. Methods We collected blood samples from 2268 individuals of 66 bird species along a reef‐to‐ridgetop tropical elevational gradient covering ~3000 m of elevation. We used molecular methods to screen samples for haemosporidian parasites, and sequenced 70% of positive infections to determine the identity of parasite genera. We fit a phylogenetic generalized mixed‐effects model to test whether infection prevalence was higher at low elevations, as predicted by the biotic interactions hypothesis. Finally, we tested for phylogenetic signal in parasite prevalence and in host elevational distribution using Pagel's λ . Results Overall parasite prevalence was 45% . Infection prevalence decreased with elevation, though prevalence remained above ~30% even for high‐elevation communities between 2000 and 3000 m. We found strong phylogenetic signal in infection prevalence, but no phylogenetic signal in host elevational distribution. Nearly all sequenced infections (97%) were of Haemoproteus. Main Conclusions Our results are consistent with predictions arising from the biotic interactions hypothesis. However, phylogenetic relationships among hosts are a much better predictor of infection prevalence than is elevational position: closely related bird species tend to have similar infection prevalence regardless of the elevations where they live.

Integrating Pore-Scale Flow MRI and X-ray μCT for Validation of Numerical Flow Simulations in Porous Sedimentary Rocks - K. Karlsons; D. W. de Kort; F. O. Alpak; J. Dietderich; J. J. Freeman; M. Appel; M. D. Mantle; A. J. Sederman; L. F. Gladden (Transport in Porous Media, 2022)
Single-phase fluid flow velocity maps in Ketton and Estaillades carbonate rock core plugs are computed at a pore scale, using the lattice Boltzmann method (LBM) simulations performed directly on three-dimensional (3D) X-ray micro-computed tomography (µCT) images (≤ 7 µm spatial resolution) of the core plugs. The simulations are then benchmarked on a voxel-by-voxel and pore-by-pore basis to quantitative, 3D spatially resolved magnetic resonance imaging (MRI) flow velocity maps, acquired at 35 µm isotropic spatial resolution for flow of water through the same rock samples. Co-registration of the 3D experimental and simulated velocity maps and coarse-graining of the simulation to the same resolution as the experimental data allowed the data to be directly compared. First, the results are demonstrated for Ketton limestone rock, for which good qualitative and quantitative agreement was found between the simulated and experimental velocity maps. The flow-carrying microstructural features in Ketton rock are mostly larger than the spatial resolution of the µCT images, so that the segmented images are an adequate representation of the pore space. Second, the flow data are presented for Estaillades limestone, which presents a more heterogeneous case with microstructural features below the spatial resolution of the µCT images. Still, many of the complex flow patterns were qualitatively reproduced by the LBM simulation in this rock, although in some pores, noticeable differences between the LBM and MRI velocity maps were observed. It was shown that 80% of the flow (fractional summed z -velocities within pores) in the Estaillades rock sample is carried by just 10% of the number of macropores, which is an indication of the high structural heterogeneity of the rock; in the more homogeneous Ketton rock, 50% of the flow is carried by 10% of the macropores. By analysing the 3D MRI velocity map, it was found that approximately one-third of the total flow rate through the Estaillades rock is carried by microporosity—a porosity that is not captured at the spatial resolution of the µCT image.

Patterns of genomic diversity and linkage disequilibrium across the disjunct range of the Australian forest tree Eucalyptus globulus - Jakob B. Butler; Jules S. Freeman; Brad M. Potts; René E. Vaillancourt; Hossein V. Kahrood; Peter K. Ades; Philippe Rigault; Josquin F. G. Tibbits (Tree Genetics & Genomes, 2022)
The evolutionary trajectory of a population both influences and is influenced by characteristics of its genome. A disjunct population, for example is likely to exhibit genomic features distinct from those of continuous populations, reflecting its specific evolutionary history and influencing future recombination outcomes. We examined genetic diversity, population differentiation and linkage disequilibrium (LD) across the highly disjunct native range of the Australian forest tree Eucalyptus globulus , using 203,337 SNPs genotyped in 136 trees spanning seven races. We found support for four broad genetic groups, with moderate F ST , high allelic diversity and genome-wide LD decaying to an r 2 of 0.2 within 4 kb on average. These results are broadly similar to those reported previously in Eucalyptus species and support the ‘ring’ model of migration proposed for E. globulus . However, two of the races (Otways and South-eastern Tasmania) exhibited a much slower decay of LD with physical distance than the others and were also the most differentiated and least diverse, which may reflect the effects of selective sweeps and/or genetic bottlenecks experienced in their evolutionary history. We also show that F ST and rates of LD vary within and between chromosomes across all races, suggestive of recombination outcomes influenced by genomic features, hybridization or selection. The results obtained from studying this species serve to illustrate the genomic effects of population disjunction and further contribute to the characterisation of genomes of woody genera.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Physiological Functioning and Productivity in Eastern Cottonwood and Hybrid Poplars on Contrasting Sites in the Southeastern US - Heidi J. Renninger; Leah F. Stewart; John L. Freeman; Randall J. Rousseau (BioEnergy Research, 2022)

Responsible agriculture must adapt to the wetland character of mid‐latitude peatlands - Benjamin W. J. Freeman; Chris D. Evans; Samuel Musarika; Ross Morrison; Thomas R. Newman; Susan E. Page; Giles F. S. Wiggs; Nicholle G. A. Bell; David Styles; Yuan Wen; David R. Chadwick; Davey L. Jones (Global Change Biology, 2022)
Drained, lowland agricultural peatlands are greenhouse gas (GHG) emission hotspots and a large but vulnerable store of irrecoverable carbon. They exhibit soil loss rates of ~2.0 cm yr −1 and are estimated to account for 32% of global cropland emissions while producing only 1.1% of crop kilocalories. Carbon dioxide emissions account for >80% of their terrestrial GHG emissions and are largely controlled by water table depth. Reducing drainage depths is, therefore, essential for responsible peatland management. Peatland restoration can substantially reduce emissions. However, this may conflict with societal needs to maintain productive use, to protect food security and livelihoods. Wetland agriculture strategies will, therefore, be required to adapt agriculture to the wetland character of peatlands, and balance GHG mitigation against productivity, where halting emissions is not immediately possible. Paludiculture may substantially reduce GHG emissions but will not always be viable in the current economic landscape. Reduced drainage intensity systems may deliver partial reductions in the rate of emissions, with smaller modifications to existing systems. These compromise systems may face fewer hurdles to adoption and minimize environmental harm until societal conditions favour strategies that can halt emissions. Wetland agriculture will face agronomic, socio‐economic and water management challenges, and careful implementation will be required. Diversity of values and priorities among stakeholders creates the potential for conflict. Successful implementation will require participatory research approaches and co‐creation of workable solutions. Policymakers, private sector funders and researchers have key roles to play but adoption risks would fall predominantly on land managers. Development of a robust wetland agriculture paradigm is essential to deliver resilient production systems and wider environmental benefits. The challenge of responsible use presents an opportunity to rethink peatland management and create thriving, innovative and green wetland landscapes for everyone's future benefit, while making a vital contribution to global climate change mitigation.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Development of a Seafloor Community Classification for the New Zealand Region Using a Gradient Forest Approach - Fabrice Stephenson; Ashley A. Rowden; Tom Brough; Grady Petersen; Richard H. Bulmer; John R. Leathwick; Andrew M. Lohrer; Joanne I. Ellis; David A. Bowden; Shane W. Geange; Greig A. Funnell; Debbie J. Freeman; et al. (Frontiers in Marine Science, 2022)
To support ongoing marine spatial planning in New Zealand, a numerical environmental classification using Gradient Forest models was developed using a broad suite of biotic and high-resolution environmental predictor variables. Gradient Forest modeling uses species distribution data to control the selection, weighting and transformation of environmental predictors to maximise their correlation with species compositional turnover. A total of 630,997 records (39,766 unique locations) of 1,716 taxa living on or near the seafloor were used to inform the transformation of 20 gridded environmental variables to represent spatial patterns of compositional turnover in four biotic groups and the overall seafloor community. Compositional turnover of the overall community was classified using a hierarchical procedure to define groups at different levels of classification detail. The 75-group level classification was assessed as representing the highest number of groups that captured the majority of the variation across the New Zealand marine environment. We refer to this classification as the New Zealand “Seafloor Community Classification” (SCC). Associated uncertainty estimates of compositional turnover for each of the biotic groups and overall community were also produced, and an added measure of uncertainty – coverage of the environmental space – was developed to further highlight geographic areas where predictions may be less certain owing to low sampling effort. Environmental differences among the deep-water New Zealand SCC groups were relatively muted, but greater environmental differences were evident among groups at intermediate depths in line with well-defined oceanographic patterns observed in New Zealand’s oceans. Environmental differences became even more pronounced at shallow depths, where variation in more localised environmental conditions such as productivity, seafloor topography, seabed disturbance and tidal currents were important differentiating factors. Environmental similarities in New Zealand SCC groups were mirrored by their biological compositions. The New Zealand SCC is a significant advance on previous numerical classifications and includes a substantially wider range of biological and environmental data than has been attempted previously. The classification is critically appraised and considerations for use in spatial management are discussed.

Global patterns of resilience decline in vertebrate populations - Pol Capdevila; Nicola Noviello; Louise McRae; Robin Freeman; Christopher F. Clements (Ecology Letters, 2022)
Maintaining the resilience of natural populations, their ability to resist and recover from disturbance, is crucial to prevent biodiversity loss. However, the lack of appropriate data and quantitative tools has hampered our understanding of the factors determining resilience on a global scale. Here, we quantified the temporal trends of two key components of resilience—resistance and recovery—in >2000 population time‐series of >1000 vertebrate species globally. We show that the number of threats to which a population is exposed is the main driver of resilience decline in vertebrate populations. Such declines are driven by a non‐uniform loss of different components of resilience (i.e. resistance and recovery). Increased anthropogenic threats accelerating resilience loss through a decline in the recovery ability—but not resistance—of vertebrate populations. These findings suggest we may be underestimating the impacts of global change, highlighting the need to account for the multiple components of resilience in global biodiversity assessments.

Oklahoma Nathan Shock Aging Center — assessing the basic biology of aging from genetics to protein and function - Holly Van Remmen; Willard M. Freeman; Benjamin F. Miller; Michael Kinter; Jonathan D. Wren; Ann Chiao; Rheal A. Towner; Timothy A. Snider; William E. Sonntag; Arlan Richardson (GeroScience, 2021)

Multiscale Digital Rock Analysis for Complex Rocks - L. C. Ruspini; P. E. Øren; S. Berg; S. Masalmeh; T. Bultreys; C. Taberner; T. Sorop; F. Marcelis; M. Appel; J. Freeman; O. B. Wilson (Transport in Porous Media, 2021)

Intensity of grass invasion negatively correlated with population density and age structure of an endangered dune plant across its range - Scott F. Jones; Anna Kennedy; Chase M. Freeman; Karen M. Thorne (Biological Invasions, 2021)

Mineralogical and chemical comparison of carbonate from sites selected for cement production with limestone used in commercial operations - Freeman E. D. Senzani; Antoine F. Mulaba-Bafubiandi (Arabian Journal of Geosciences, 2021)

Risk factors associated with Ctenocephalides felis flea infestation of peri-urban goats: a neglected parasite in an under-appreciated host - Julia Rose Dahm; Jordana Burdon Bailey; Robert F. Kelly; Patrick Chikungwa; Julius Chulu; Livio Costa Junior; Emily June Freeman; Dagmar Mayer; Stella Mazeri; Neil Donald Sargison (Tropical Animal Health and Production, 2021)
Goats are critical in mixed smallholder agricultural systems in lower and middle-income countries, while fleas are important human and animal health concerns around the world. Convenience sampling was used to describe and consider risk factors for flea infestations of peri-urban goats, with the aim of informing the iterative development of animal husbandry and management based control strategies. Seven hundred and ninety-two goats were examined in 228 households across 10 peri-urban communities surrounding Blantyre in southern Malawi. The prevalence of Ctenocephalides felis fleas was 18.3, 37.1 and 100% at the levels of individual goats, households and communities, respectively, highlighting a neglected human and animal health concern. Constant introduction of new livestock coupled to a lack of biosecurity within communities, the ubiquitous presence of dog and cat hosts for C. felis , the frequency and thoroughness of cleaning overnight goat accommodation, and goat age less than 12 months old were identified as risk factors for flea infestation. This focal cross-sectional study highlights the significance of fleas in peri-urban communities and uncovers trends and commonalities that are needed to inform sustainable disease management. The majority of the peri-urban goat keepers were female, had resided in the same community throughout their whole life and had primary level education. Advice on the planned management of fleas in livestock needs to be tailored towards this demographic group. This approach affords an opportunity to promote public health measures to address household flea infestations and zoonotic disease spread.

Climate change impacts on human health at an actionable scale: a state-level assessment of Indiana, USA - G. M. Filippelli; J. L. Freeman; J. Gibson; S. Jay; M. J. Moreno-Madriñán; I. Ogashawara; F. S. Rosenthal; Y. Wang; E. Wells (Climatic Change, 2020)

Global changes may be promoting a rise in select cyanobacteria in nutrient‐poor northern lakes - Erika C. Freeman; Irena F. Creed; Blake Jones; Ann‐Kristin Bergström (Global Change Biology, 2020)
The interacting effects of global changes—including increased temperature, altered precipitation, reduced acidification and increased dissolved organic matter loads to lakes—are anticipated to create favourable environmental conditions for cyanobacteria in northern lakes. However, responses of cyanobacteria to these global changes are complex, if not contradictory. We hypothesized that absolute and relative biovolumes of cyanobacteria (both total and specific genera) are increasing in Swedish nutrient‐poor lakes and that these increases are associated with global changes. We tested these hypotheses using data from 28 nutrient‐poor Swedish lakes over 16 years (1998–2013). Increases in cyanobacteria relative biovolume were identified in 21% of the study sites, primarily in the southeastern region of Sweden, and were composed mostly of increases from three specific genera: Merismopedia , Chroococcus and Dolichospermum . Taxon‐specific changes were related to different environmental stressors; that is, increased surface water temperature favoured higher Merismopedia relative biovolume in low pH lakes with high nitrogen to phosphorus ratios, whereas acidification recovery was statistically related to increased relative biovolumes of Chroococcus and Dolichospermum . In addition, enhanced dissolved organic matter loads were identified as potential determinants of Chroococcus suppression and Dolichospermum promotion. Our findings highlight that specific genera of cyanobacteria benefit from different environmental changes. Our ability to predict the risk of cyanobacteria prevalence requires consideration of the environmental condition of a lake and the sensitivities of the cyanobacteria genera within the lake. Regional patterns may emerge due to spatial autocorrelations within and among lake history, rates and direction of environmental change and the niche space occupied by specific cyanobacteria.

A pharmacokinetic-pharmacodynamic assessment of oral antibiotics for pyelonephritis - J. W. S. Cattrall; E. Asín-Prieto; J. Freeman; I. F. Trocóniz; A. Kirby (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Cancer incidence in the Agricultural Health Study after 20 years of follow-up - Catherine C. Lerro; Stella Koutros; Gabriella Andreotti; Dale P. Sandler; Charles F. Lynch; Lydia M. Louis; Aaron Blair; Christine G. Parks; Srishti Shrestha; Jay H. Lubin; Paul S. Albert; Jonathan N. Hofmann; et al. (Cancer Causes & Control, 2019)

Global change‐driven effects on dissolved organic matter composition: Implications for food webs of northern lakes - Irena F. Creed; Ann‐Kristin Bergström; Charles G. Trick; Nancy B. Grimm; Dag O. Hessen; Jan Karlsson; Karen A. Kidd; Emma Kritzberg; Diane M. McKnight; Erika C. Freeman; Oscar E. Senar; Agneta Andersson; et al. (Global Change Biology, 2018)
Northern ecosystems are experiencing some of the most dramatic impacts of global change on Earth. Rising temperatures, hydrological intensification, changes in atmospheric acid deposition and associated acidification recovery, and changes in vegetative cover are resulting in fundamental changes in terrestrial–aquatic biogeochemical linkages. The effects of global change are readily observed in alterations in the supply of dissolved organic matter ( DOM )—the messenger between terrestrial and lake ecosystems—with potentially profound effects on the structure and function of lakes. Northern terrestrial ecosystems contain substantial stores of organic matter and filter or funnel DOM , affecting the timing and magnitude of DOM delivery to surface waters. This terrestrial DOM is processed in streams, rivers, and lakes, ultimately shifting its composition, stoichiometry, and bioavailability. Here, we explore the potential consequences of these global change‐driven effects for lake food webs at northern latitudes. Notably, we provide evidence that increased allochthonous DOM supply to lakes is overwhelming increased autochthonous DOM supply that potentially results from earlier ice‐out and a longer growing season. Furthermore, we assess the potential implications of this shift for the nutritional quality of autotrophs in terms of their stoichiometry, fatty acid composition, toxin production, and methylmercury concentration, and therefore, contaminant transfer through the food web. We conclude that global change in northern regions leads not only to reduced primary productivity but also to nutritionally poorer lake food webs, with discernible consequences for the trophic web to fish and humans.

Dissociable effects of the kappa opioid receptor agonist nalfurafine on pain/itch-stimulated and pain/itch-depressed behaviors in male rats - Matthew L. Lazenka; Megan J. Moerke; E. Andrew Townsend; Kevin B. Freeman; F. Ivy Carroll; S. Stevens Negus (Psychopharmacology, 2018)

The neuronal metabolite NAA regulates histone H3 methylation in oligodendrocytes and myelin lipid composition - N. K. Singhal; H. Huang; S. Li; R. Clements; J. Gadd; A. Daniels; E. E. Kooijman; P. Bannerman; T. Burns; F. Guo; D. Pleasure; E. Freeman; et al. (Experimental Brain Research, 2017)

Comparison of trends in butterfly populations between monitoring schemes - D. B. Roy; E. F. Ploquin; Z. Randle; K. Risely; M. S. Botham; I. Middlebrook; D. Noble; K. Cruickshanks; S. N. Freeman; T. M. Brereton (Journal of Insect Conservation, 2015)

Association mapping for wood quality and growth traits in Eucalyptus globulus ssp. globulus Labill identifies nine stable marker-trait associations for seven traits - Saravanan Thavamanikumar; Luke J. McManus; Peter K. Ades; Gerd Bossinger; Desmond J. Stackpole; Richard Kerr; Sara Hadjigol; Jules S. Freeman; René E. Vaillancourt; Peng Zhu; Josquin F. G. Tibbits (Tree Genetics & Genomes, 2014)

The Madagascar Fauna and Flora Group as an example of how a consortium is enabling diverse zoological and botanical gardens to contribute to biodiversity conservation in Madagascar - K. L. M. Freeman; A. Bollen; F. J. F. Solofoniaina; H. Andriamiarinoro; I. Porton; C. R. Birkinshaw (Plant Biosystems, 2014)

Characterization of Fusarium mangiferae isolates from mango malformation disease in Southern Spain - M. Crespo; E. Arrebola; F. M. Cazorla; M. Maymon; S. Freeman; J. A. Torés; A. de Vicente (European Journal of Plant Pathology, 2014)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Does concentrating chemical defenses within specific regions of marine sponges result in enhanced protection from predators? - Christopher J. Freeman; Daniel F. Gleason (Hydrobiologia, 2012)

Infrasound in the flutter-jump display of Capercaillie (Tetrao urogallus): signal or artefact? - Angela R. Freeman; James F. Hare (Journal of Ornithology, 2011)

Body mass index, effect modifiers, and risk of pancreatic cancer: a pooled study of seven prospective cohorts - Li Jiao; Amy Berrington de Gonzalez; Patricia Hartge; Ruth M. Pfeiffer; Yikyung Park; D. Michal Freedman; Mitchell H. Gail; Michael C. R. Alavanja; Demetrius Albanes; Laura E. Beane Freeman; Wong-Ho Chow; Wen-Yi Huang; et al. (Cancer Causes & Control, 2010)

Chemical defenses, nutritional quality, and structural components in three sponge species: Ircinia felix, I. campana, and Aplysina fulva - Christopher J. Freeman; Daniel F. Gleason (Marine Biology, 2010)

Appraising the roles of nutrient availability, global change, and functional traits during the angiosperm rise to dominance - Kevin E. Mueller; Aaron F. Diefendorf; Katherine H. Freeman; David M. Eissenstat (Ecology Letters, 2010)
Ecology Letters (2010) 13: E1–E6 Abstract To explain the rise of angiosperms during the Cretaceous, Berendse & Scheffer ( Ecol. Lett. , 12, 2009, 865) invoke feedbacks between leaf litter, soil nutrients, and growth, overlooking other factors affecting resource acquisition by Cretaceous plants. We evaluate their hypothesis, highlight alternative explanations, and emphasize use of a broader framework for understanding the angiosperm radiation.

The distribution and host range of the pandemic disease chytridiomycosis in Australia, spanning surveys from 1956–2007 - Kris Murray; Richard Retallick; Keith R. McDonald; Diana Mendez; Ken Aplin; Peter Kirkpatrick; Lee Berger; David Hunter; Harry B. Hines; R. Campbell; Matthew Pauza; Michael Driessen; et al. (Ecology, 2010)
Chytridiomycosis is the worst disease to affect vertebrate biodiversity on record. In Australia, it is thought to have caused the extinction of four frog species, and it threatens the survival of at least 10 more. We report the current distribution and host range of this invasive disease in Australia, which is essential knowledge for conservation management. We envisage that the data be used in a global and national context for predictive modeling, meta‐analyses, and risk assessment. Our continent‐wide data set comprises 821 sites in Australia and includes 10 183 records from >80 contributors spanning collection dates from 1956 to 2007. Sick and dead frogs from the field and apparently healthy frogs from museum collections were tested opportunistically for the presence of Batrachochytrium dendrobatidis , the fungal pathogen causing chytridiomycosis, and apparently healthy frogs and tadpoles found during surveys were tested purposively. The diagnostic tests used were histology of skin samples and quantitative PCR of skin swabs. Chytridiomycosis was found in all Australian states and the Australian Capital Territory, but not in the Northern Territory. Currently it appears to be confined to the relatively cool and wet areas of Australia, such as along the Great Dividing Range and adjacent coastal areas in the eastern mainland states of Queensland, New South Wales, and Victoria, eastern and central Tasmania, southern South Australia, and southwestern Western Australia. Batrachochytrium dendrobatidis may have been introduced into Australia via the port of Brisbane around 1978 and spread northward and southward. It did not appear to arrive in Western Australia until 1985. The earliest records from South Australia and Tasmania are from 1995 and 2004, respectively, although archival studies from these states are lacking. We also report negative findings showing that the disease does not currently occur in some areas that appear to be environmentally suitable, including Cape York Peninsula in Queensland and most of the World Heritage Area in western Tasmania. Infection with B. dendrobatidis has been recorded from 63 frog species in Australia to date, all belonging to the Hylidae, Limnodynastidae, and Myobatrachidae, with the exception of one individual of a species from the Microhylidae and the introduced cane toad of the family Bufonidae. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

The role of selenium in protecting plants against prairie dog herbivory: implications for the evolution of selenium hyperaccumulation - Colin F. Quinn; John L. Freeman; Miriam L. Galeas; Erin M. Klamper; Elizabeth A. H. Pilon-Smits (Oecologia, 2008)

The self-incompatibility locus (S) and quantitative trait loci for self-pollination and seed dormancy in sunflower - Sonali D. Gandhi; Adam F. Heesacker; Carrie A. Freeman; Jason Argyris; Kent Bradford; Steven J. Knapp (Theoretical and Applied Genetics, 2005)

Early and late patterns of stimulus-related activity in auditory cortex of trained animals - F. W. Ohl; M. Deliano; H. Scheich; W. J. Freeman (Biological Cybernetics, 2003)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Spectroscopic identification of a dinuclear metal centre in manganese(II)-activated aminopeptidase P from Escherichia coli: implications for human prolidase - Lianbo Zhang; Maxwell J. Crossley; Nicholas E. Dixon; Paul J. Ellis; Megan L. Fisher; Glenn F. King; Penelope E. Lilley; Dugald MacLachlan; Ronald J. Pace; H. C. Freeman (JBIC Journal of Biological Inorganic Chemistry, 1998)

Peroxidase-Catalyzed Oxidation of 2,4,6-Trichlorophenol - F. W. Wiese; H. C. Chang; R. V. Lloyd; J. P. Freeman; V. M. Samokyszyn (Archives of Environmental Contamination and Toxicology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

The 18th congress of the israeli phytopathological society - Y. Elad; D. Shtienberg; H. Vintal; Y. Cohen; Sonia Farkash; Zipora Reshit; A. Baider; Edna Levy; I. S. Ben-Ze’ev; Y. Nitzani; Frieda Kleitman; Talma Katan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

A histopathological examination of, and analysis for polychlorinated hydrocarbons in, inshore Atlantic cod (Gadus morhua) - H. C. Freeman; G. B. Sangalang; J. F. Uthe; E. T. Garside; P. G. Daye (Archives of Environmental Contamination and Toxicology, 1983)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)